Field guide to snow - Sturm, Matthew, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2020)
Over my career I have led more than 30 snow expeditions, taught snow science in the classroom at the undergraduate and graduate level, and run more than a dozen field method classes all over the U.S. In the field with my students, we have worked shoulder-to-shoulder in snow pits measuring the density, grain size, and stratigraphy of the snow pack. In that setting I have tried to teach people how to read in the snow the story of the winter. Most beginners at first have trouble seeing the story: it is all just white and the same. But with time, and a little guidance, the winter world has opened up for them. That is what this book is about: just a little guidance for those who might not get a chance to dig a snow pit with me, but who want to know more about the snow.--Provided by publisher.
Where Is Snow? -- The Crystal Factory -- Snowflakes -- Snow Layers and Weather -- Metamorphism: Snow in the Crucible -- The Great White Blanket -- Snow and Living Things.
Keywords: Snow